Effectiveness and Design of PBL-Based Project Approach for Non-Major University Computing Courses - Jung-In Choi; Sooyeon Yang (Applied Sciences)
The purpose of this study is to analyze the learning outcomes and educational implications of introducing a new Problem-Based Learning project approach in a computing course for non-major students. The Problem-Based Learning project approach, designed by the research team, provides a teaching and learning strategy in which students collaborate to analyze and extend code within real-world problem contexts while systematically exchanging feedback. The study was conducted as a case study involving two groups of students: a control group comprising 30 students following traditional instructional methods and an experimental group consisting of 31 students employing the proposed approach. Educational outcomes were evaluated through both quantitative and qualitative analyses. The findings demonstrate that the Problem-Based Learning project approach facilitated a significantly more effective learning experience, fostering key skills such as communication, collaboration, and problem-solving. Furthermore, substantial improvements were observed in instructional effectiveness and the structure of practical activities. These findings suggest that the Problem-Based Learning project approach mirrors real-world practices, equipping students with essential computational thinking skills and a deeper understanding of foundational topics such as Python, data structures, and algorithms. This study provides valuable insights for the development of instructional strategies in computing courses for non-major students, emphasizing the importance of creating systematic learning environments that bridge theoretical knowledge and practical application through real-world problem-solving activities.